THE IMPACT OF DECREASING TOURIST VISITS ON CARBON MONOXIDE (CO) LEVELS IN YOGYAKARTA - Fauzi, Naufal Annas (Jurnal Pendidikan Vokasi Otomotif, 2023)
The impact of the spread of the coronavirus disease (COVID 19) affects all people in the world. One of the efforts by the Indonesian government to reduce the spread of the virus is by implementing Large-Scale Social Restrictions (PSBB). The impact of the PSBB can be felt directly by the community in various sectors. The existence of regulations regarding restrictions on large-scale social activities (PSBB) has resulted in a decrease in activity in all fields, one of which is tourism in the Special Region of Yogyakarta. The positive side that can be drawn from social restriction regulations is the potential for reducing pollutants that pollute urban air caused by human activities. This study analyzes data from air quality testing results in the City of Yogyakarta from the Ministry of Environment (KLH) and the number of tourists visiting Yogyakarta from the Yogyakarta City Tourism Office in 2019 to 2020. Based on data obtained from the Yogyakarta City Tourism Office from 2019 to 2019 2020 saw an average decrease in tourist visits by 70% at three tourist sites in the city of Yogyakarta, namely: the Yogyakarta Palace, Taman Pintar, and the Vredeburg Museum. Based on data obtained from the Yogyakarta Special Region Tourism Statistics Report for 2019 and 2020, there has been an average decrease in tourist visits by 71% at ten tourist sites in the City of Yogyakarta. The decrease in tourist visits affects the air quality in the Yogyakarta City environment. This can be proven by improving the quality of ambient air in the City of Yogyakarta in 2020. Reducing the level of carbon monoxide (CO) in the air in the city of Yogyakarta by 12.5%.